2017
DOI: 10.1007/s11695-017-2997-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 6 and 12 months Duodenal-Jejunal Bypass Liner Treatment on Obesity and Type 2 Diabetes: a Crossover Cohort Study

Abstract: Objective The aim of this research was to study the duodenaljejunal bypass liner (DJBL) treatment for obesity and type 2 diabetes mellitus (T2DM) in patients after dietary treatment in a cross-over design. Background DJBL treatment has been proven effective for treatment of obesity and T2DM. However, data on safety and efficacy of a 12-month DJBL treatment is limited. Methods In 2014, our research group reported on a multicenter randomized clinical trial. Patients were randomized to DJBL or dietary treatment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Of these, 753 articles were excluded, resulting in 60 that met the selection criteria and 5603 enrolled participants (of whom 5261 were analyzed). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 753 articles were excluded, resulting in 60 that met the selection criteria and 5603 enrolled participants (of whom 5261 were analyzed). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 90% of the studies were in populations with metabolic disease or conditions associated with metabolic disease: obesity, 25 , 32 , 33 , 34 , 37 , 41 , 43 , 45 , 47 , 48 , 49 , 52 , 57 , 58 , 59 , 60 , 62 , 63 , 64 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 76 , 77 , 79 , 80 , 81 , 82 , 83 diabetes or prediabetes, 26 , 32 , 38 , 46 , 59 hypertension, 40 coronary artery disease, 65 dyslipidemia, 51 chronic kidney disease, 78 nonalcoholic fatty liver disease, 31 , 35 Cushing disease, 36 polycystic ovary syndrome, 61 breast cancer, 28 , 56 , 82 and aging (ie, college students 84 ). Of the patients in these 54 studies, 22 (41%) had undergone bariatric surgery as the studied intervention (n = 14) or as part of the required eligibility criteria (n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diabetes remission outcomes following a stand-alone foregut exclusion procedure, such as duodenal-jejunal bypass (DJB), remains inconclusive. While some studies have reported that DJB resulted in effective anti-diabetic outcomes 5,6 , several other studies have also suggested that DJB is still ineffective to induce diabetes remission 710 . The unconvincing reports on the anti-diabetic effect of DJB is interesting because RYGB continued to demonstrate significant diabetes remission outcomes 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical implications of such a classifier can be varied and diverse. Changes in glucose dynamics could be correlated with other anthropometric, biochemical or hormonal characteristics [ 44 , 45 ] in order to try to anticipate the rate and intensity of metabolic improvements after the exclusion and better understand the possible mechanisms of its effects. It could also be used as a screening tool for patient/treatment selection.…”
Section: Introductionmentioning
confidence: 99%